Pengaruh Dividend Payout Ratio Dan Dividend Yield Terhadap Nilai Perusahaan Properti Di Bursa Efek Indonesia (BEI) Periode Tahun 2017-2019 - Arum, Puspita Mawar; Rahayu, Sri Retnaning (Universitas Muhammadiyah Metro, 2022)
Based on field findings, the problem that occurs is the occurrence of stock price fluctuations that affect the exchange rate. In connection with these problems, the formulation of the problem in this study is whether the Dividend Payout Ratio and Dividend Yield together have a positive and significant effect on the value of property companies on the Indonesia Stock Exchange. The purpose of this study is to determine whether the Dividend Payout Ratio and Dividend Yield collectively, it has a positive and significant effect on the value of property companies on the Indonesia Stock Exchange.This research is quantitative research. With this type of ex-post facto research. Ex-post facto research is a study that is conducted to examine events that have occurred and then trace them backwards to find out the factors that can cause these incidents. The technique of determining the sample using purposive sampling technique. The results of the study using the t test (partial) show the value of the effect of the dividend payout ratio on firm value, namely tcount> ttable (3.301> 1.688), and the value of the effect of dividend yield on firm value is tcount> ttable (2,210> 1,688). While the f (simultaneous) test shows the value of the effect of the dividend payout ratio and dividend yield simultaneously on the firm value, namely Fcount 6.208 Ftable 3.259. From the calculation of the R square value, the ability of the independent variables to explain the variance of the dependent variable is 25.8%, which means that 74.2% is influenced by other factors not examined in this study.